Turbulent National Identity in Laos: The Hmong Ethnic Group as a Case Study - Resminingayu, Dewi Hermawati (Paradigma: Jurnal Kajian Budaya, 2018)
Since the independence, Laos has changed its national identity based on different principles namely Buddhism, Socialism and Consolidation between Buddhism and Socialism. These changes have given dynamic impacts to the identity of the people not only from their political life but also from socio-cultural life. This paper will specifically discuss the impacts undergone by the Hmong as one of the ethnic minorities that are often excluded from the discussion of ethnic groups in Laos. The discussion uses three approaches of ethnicity, namely Primordialism, Instrumentalism, and Constructivism in order to explain the dynamic identity of the Hmong. This paper argues that ethnic identity is always changing since it depends on the strength of power and resistance towards the assignation and assertion of meanings.